PTH-061 Vitamin D is associated with an increased risk of oesophageal adenocarcinoma but not its pre-cursor conditions. (23rd September 2015) - Mulholland, H G; Cantwell, M M; Anderson, L A; Johnston, B T; Watson, R G P; Murray, L J
Abstract : Introduction: Evidence is accumulating that vitamin D may be protective against the development of many cancers.1 There are notable exceptions in the literature though, demonstrating increased risks of oesophageal squamous cell carcinoma and oesophageal squamous dysplasia for individuals with the highest serum concentrations of 25-hydroxyvitamin D.2 3 Our aim was to explore the association between dietary vitamin D and related nutrients and the risk of oesophageal adenocarcinoma (OAC) and its pre-cursor conditions, Barrett's oesophagus (BO) and reflux oesophagitis (RO). Methods: In an all-Ireland case-control study conducted between March 2002 and July 2005, 218 OAC patients, 212 long-segment BO patients, 208 RO patients and 252 healthy population-based controls completed a 101-item food frequency questionnaire, in addition to providing other lifestyle information and medical histories. Multiple logistic regression analysis was applied to examine the association between vitamin D, calcium and dairy intake and disease risk, prior to and after adjustment for potential confounders. Stratified analyses were also conducted by body mass index status. Results: OAC risk was significantly greater for individuals in the highest compared with the lowest tertile of vitamin D intake (OR 1.99, 95% CI 1.03 to 3.86, p for trend=0.02) after adjustment for potential confounders. This elevated risk appeared to be accentuated in overweight (OR 2.49, 95% CI 1.16 to 5.37) OAC patients, although formal tests for interaction were not significant. Vitamin D intake was unrelated to RO and BO risk. There were no significant associations observed for calcium or dairy intake and RO, BO or OAC risk. Conclusion: A significant direct association was observed between vitamin D intake and OAC risk, which concurs with previous findings for oesophageal squamous cell carcinoma. Vitamin D intake was unrelated to RO and BO risk. No significant associations were found between calcium or dairy intake and the risk of these oesophageal lesions. Further research is needed before recommendations to establish dietary vitamin D guidelines are implemented.